Strains, Mechanism, and Perspective: Salmonella-Based Cancer Therapy - Cheng-Zhi Wang; Robert A. Kazmierczak; Abraham Eisenstark (International Journal of Microbiology)
Recently, investigation of bacterial-based tumor therapy has regained focus due to progress in molecular, cellular, and microbial biology. Many bacteria such as Salmonella, Listeria, Escherichia, and Clostridium have proved to have tumor targeting and in some cases even tumor-destroying phenotypes. Furthermore, bacterial clinical treatments for cancer have been improved by combination with other therapeutic methods such as chemotherapeutic drugs and radioactive agents. Synthetic biology techniques have also driven the development of new bacterial-based cancer therapies. However, basic questions about the mechanisms of bacterial-mediated tumor targeting and destruction are still being elucidated. In this review, we focus on three tumor-therapeutic Salmonella models, the most intensively studied bacterial genus in this field. One of these Salmonella models is our Salmonella enterica serovar Typhimurium LT2 derived strain CRC2631, engineered to minimize toxicity but maximize tumor-targeting and destruction effects. The other two are VNP20009 and A1-R. We compare the means by which these therapeutic candidate strain models were selected for study, their tumor targeting and tumor destruction phenotypes in vitro and in vivo, and what is currently known about the mechanisms by which they target and destroy tumors.